Comparative analysis of seed proteome of Glycine max and Glycine soja. Issue 3 (29th April 2020) - Hashiguchi, Takuyu; Hashiguchi, Masatsugu; Tanaka, Hidenori; Gondo, Takahiro; Akashi, Ryo
Abstract: Soybean, a globally important grain legume, contains large amounts of proteins, lipids, and secondary metabolites and, when ingested, has a wide array of physiological functions that may improve human health. In the development of cultivated soybean [ Glycine max (L.) Merr.] with improved abiotic and biotic stress resistance, high yield, and seed quality, wild soybean ( Glycine soja Siebold & Zucc.) has been an excellent source of germplasm, owing to its genetic diversity. Although genomic differences between the two species have been intensively studied, the differences in seed protein expression remain poorly understood. In the present study, we used a shotgun proteomic comparative analysis approach to further characterize the seed proteome in cultivated and wild soybean. Protamine sulfate‐mediated precipitation successfully decreased the levels of two major proteins that had previously masked the detection of low‐abundant proteins. We identified 65 differentially expressed proteins between the two species, with 39 proteins expressed more highly in G. soja and 26 proteins expressed more highly in G. max . Among these proteins, various stress tolerance‐related proteins were found in wild soybean, perhaps reflecting its adaptation to diverse ecological conditions. Cultivated soybean expressed high levels of sucrose and lipid biosynthesis proteins, and this was also confirmed at the transcriptional level. Bioinformatic analyses revealed that cellular and metabolic process was the functional category most frequently linked to the differentially expressed proteins. These data provide valuable information that will contribute to a better understanding of soybean seed biology and help to promote G. max breeding for improved agronomic traits using wild relatives.